Amino acid synthesis in chloroplasts - Lea, Peter; Mazzafera, Paulo; Azevedo, Ricardo (Henry Stewart Talks, 2007)
Nitrate and ammonium uptake, Ammonium assimilation, Synthesis of aspartate-dependent amino acids, Synthesis of branched chain amino acids, Synthesis of aromatic amino acids, Regulation of amino acid metabolism